Roseola infantum and other syndromes associated with acute HHV6 infection. Issue 12 (December 1990) - Irving, W L; Chang, J; Raymond, D R; Dunstan, R; Grattan-Smith, P; Cunningham, A L
Abstract : Eight cases of acute human herpesvirus type 6 (HHV6) infection in infants were diagnosed serologically by the demonstration of IgM anti-HHV6 (8/8) and a significant change in total anti-HHV6 antibody titre (6/8). Four infants were sufficiently ill to require admission to hospital and further investigations: one with encephalitis and three with gross hepatosplenomegaly, two of whom had evidence of simultaneous infection with another herpes-virus. The remaining four infants had an illness compatible with roseola infantum, although this diagnosis had not been made clinically. Sera from two of those infants with rash had been sent for analysis to exclude rubella because the infants' mothers were pregnant. The other two had received antibiotics when febrile, and the subsequent appearance of the roseola rash had raised the possibility of antibiotic allergy. The data suggest that there are clinical syndromes in addition to roseola infantum associated with the presence of IgM anti-HHV6, in which serological screening for evidence of acute HHV6 infection may be useful.